Assessment of Temperature Variability Effect on Rice Production in Nasarawa State, Nigeria - Oladeinde Stephen Olufemi; Magaji I. Joshua; Ekpo Abraham Salamatu (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
The output of cereal farmlands is imperative for sustainable global food security. Quantity of production from cereal croplands are partly a function of climatic elements and are connected to the pulses of climatic variation. Hence, this paper assessed temperature variability effect on rice production in Nasarawa State, Nigeria. Daily maximum and minimum temperature data were obtained from the Nigerian Meteorological Agency and converted into monthly averages while annual rice production data was obtained from the office of Nasarawa State’s Agricultural Development Programme. Acquired data were analysed using Linear Multiple Regression Model, coefficient of variation and spatial data analysis techniques. Although rice production in the State is being affected by the fluctuations in both minimum and maximum monthly temperature, the later poses grave concern for sustainability of rice production with a negative effect size of -3.145 and a coefficient value of -191,324.30 metric tons. This negative impact of maximum temperature fluctuations on rice production indicates that rice production in Nasarawa State is vulnerable to climate variability with increasing maximum temperature. LGAs in the south senatorial district has more favourable locations for rice production in comparison to those in the North and West districts given that less temperature fluctuation was observed in the former. Government and non-governmental institutions as well as individuals planning to establish rice farm project(s) in the study area should consider doing so in the South Senatorial District in order to avoid the adverse effect of temperature variability.